The Study of Neurocognitive Outcomes, Radiological and Retinal Effects of Aspirin in Sleep Apnoea- rationale and methodology of the SNORE-ASA study - Ward, Stephanie Alison; Storey, Elsdon; Woods, Robyn L.; Hamilton, Garun S.; Kawasaki, Ryo; Janke, Andrew L.; Naughton, Matthew T.; O'Donoghue, Fergal; Wolfe, Rory; Wong, Tien Y.; Reid, Christopher M.; Abhayaratna, Walter P.; et al. (Contemporary Clinical Trials, 2018)
Sleep disordered breathing (SDB) is highly prevalent in older adults. Increasing evidence links SDB to the risk of dementia, mediated via a number of pathways, some of which may be attenuated by low-dose aspirin. This study will evaluate, in a healthy older cohort, the prospective relationship between SDB and cognitive function, changes in retinal and cerebral microvasculature, and determine whether low-dose aspirin ameliorates the effects of SDB on these outcomes over 3years. SNORE-ASA is a sub-study of the ASPirin in Reducing Events in the Elderly (ASPREE) randomised, multi-centre, placebo-controlled trial evaluating the effect of daily 100mg aspirin on disability-free and dementia-free survival in the healthy older adult aged 70 and over. At baseline, 1400 ASPREE participants successfully underwent a home sleep study with a home sleep study screening device for SDB; and 296 underwent both 1.5 Tesla brain magnetic resonance imaging (MRI) and retinal vascular imaging (RVI). Cognitive testing, brain MRI and RVI is being repeated after 3years. Change in the modified mini-mental state examination score. Secondary outcome measures are changes in other cognitive tests, and changes in abnormal parameters on RVI and volume of white matter hyper-intensities on brain MRI. Identifying preventive therapies for delaying the onset of dementia is of paramount importance. The results of this study will help clarify the impact of the SDB on risk of cognitive decline and cerebral small vessel disease, and whether low-dose aspirin can ameliorate cognitive decline in the setting of SDB. The Principal ASPREE study is registered with the International Standardized Randomized Controlled Trials Register, ASPirin in Reducing Events in the Elderly, Number: ISRCTN83772183 and clinicaltrials.gov Number NCT01038583.